2D trajectory estimation during free walking using a tiptoe-mounted inertial sensor. Issue 10 (16th July 2015) - Sagawa, Koichi; Ohkubo, Kensuke
Abstract: An estimation method for a two-dimensional walking trajectory during free walking, such as forward walking, side stepping and backward walking, was investigated using a tiptoe-mounted inertial sensor. The horizontal trajectory of the toe-tip is obtained by double integration of toe-tip acceleration during the moving phase in which the sensor is rotated before foot-off or after foot-contact, in addition to the swing phase. Special functions that determine the optimum moving phase as the integral duration in every one step are developed statistically using the gait cycle and the resultant angular velocity of dorsi/planter flexion, pronation/supination and inversion/eversion so that the difference between the estimated trajectory and actual one gives a minimum value during free walking with several cadences. To develop the functions, twenty healthy volunteers participated in free walking experiments in which subjects performed forward walking, side stepping to the right, side stepping to the left, and backward walking at 39 m down a straight corridor with several predetermined cadences. To confirm the effect of the developed functions, five healthy subjects participated in the free walking experiment in which each subject performed free walking with different velocities of normal, fast, and slow based on their own assessment in a square course with 7 m side. The experimentally obtained results of free walking with a combination of forward walking, backward walking, and side stepping indicate that the proposed method produces walking trajectory with high precision compared with the constant threshold method which determines swing phase using the size of the angular velocity.